2020
DOI: 10.21203/rs.3.rs-45405/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Use of masks in public places in Poland during SARS-Cov-2 epidemic: a  covert observational study

Abstract: Background: Face masks protect against SARS-Cov-2, however, if used incorrectly masks may increase transmission risk. Many countries, including Poland, recommend masks in pandemic control plans. In Poland, obligatory wearing of masks in public spaces was introduced on April 10th, 2020 [18]; a relaxation of previous universal measures was announced on May 29th, 2020, limiting use to indoor public spaces.Objective: to assess use of masks or other protective devices in public spaces in Poland during the SARS-Cov-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
3
1
Order By: Relevance
“…It was found that women adapt better to protective behaviors such as mask use than men, which is consistent with many studies (12)(13)(14). Similar to our study, it was demonstrated in different studies that the rate of mask compliance increased correlated with the increase in education level (15,16) (5,7,8).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was found that women adapt better to protective behaviors such as mask use than men, which is consistent with many studies (12)(13)(14). Similar to our study, it was demonstrated in different studies that the rate of mask compliance increased correlated with the increase in education level (15,16) (5,7,8).…”
Section: Discussionsupporting
confidence: 92%
“…Since airborne transmission of COVID-19 infection is considered the main route of transmission, especially in dentistry, barrier protection equipment, including goggles, masks, gloves, caps, face shields, and protective outerwear, is highly recommended for all healthcare settings (3). There were quite different rates ranging from 41.2% to 73.6% for mask use in different studies (12)(13)(14). The majority of participants (77.4%) in our study adapted to mask use in the proper area.…”
Section: Discussioncontrasting
confidence: 53%
“…In sample size calculation, maximum proportion (50%) was considered. It is because there was no previous study done in the study area about awareness status of the community about COVID- 19.…”
Section: Sampling Proceduresmentioning
confidence: 96%
“…The related study done in Ethiopia, there is still a big issue in preventing and control the pandemic because most of the community assumed that the disease cease, and the general public has little understanding or awareness about the disease (15). Communities must save themselves and others from COVID-19 by considering the following important habits such as regular hand washing ,use sanitizers, avoid touching their faces ,practice covering their mouths, noises at any time while coughing and sneezing, keep physical distance and isolate themselves if any feeling of illness and the like (16)(17)(18)(19). Ethiopia is now sharing a major proportion of the global burden of infectious diseases, while the patterns of COVID-19 are still at an earlier stage of the epidemiology curve.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the rate of mask-wearing in public in Poland, which observed 2,353 people over 3 days, found that 65-75% of people wore masks. (25) Other studies used series of photographs to estimate rates of mask wearing from 3-5 April 2020, and they found rates in Cambodia, Peru, India, Mexico, and USA of 97%, 86%, 41%, 25%, and 21% respectively. (26, 27) Facemask wearing in France, Iran, and Hong Kong was reported at 56.4%, 45.6%, and 87% respectively.…”
Section: Global Comparisonmentioning
confidence: 99%